Team Change and Its Relation to Leadership and Organization - Finik kharianti; Nuri Aslami (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
In this competitive age, organizations are facing dynamic and fast-moving environments such as technological trends, rapid social changes, more and more changing demands, globalization, and economic changes. So, this competitive environment is forcing businesses to adopt changes and change the way they do business, in order to survive and stay competitive in this business world. The purpose of this study is to provide an understanding of team change and its effects on organization and leadership. The research method used is descriptive qualitative. The results of the research show that changes are implemented at three different levels, individual, group and organizational according to changing trends, technology, customer preferences and future problems. But the adoption of change requires some practical steps in an organization to motivate employees because most of the employees do not accept the change and resist it. This is the main reason organizations fail to adopt change.